Incubation of Oxycodone Craving Following Adult-Onset and Adolescent-Onset Oxycodone Self-Administration in Male Rats - Altshuler, Rachel D.; Garcia, Kristine T.; Li, Xuan (Frontiers in Behavioral Neuroscience, 2021)
Relapse is a major obstacle to curb the ongoing epidemic of prescription opioid abuse. We and others previously demonstrated that oxycodone seeking in adult rats progressively increases after abstinence from oxycodone self-administration (incubation of oxycodone craving). In humans, the onset of oxycodone use in adolescents may increase individuals’ vulnerability to later opioid addiction. However, little is known about incubation of oxycodone craving after adolescent-onset oxycodone self-administration in rats. In the first study, we trained single-housed adolescent (postnatal day 35 at start) and adult (postnatal day 77 at start) male Sprague Dawley rats to self-administer oxycodone (0.1 mg/kg/infusion, 6 h/d for 10 d), and then tested oxycodone relapse on both abstinence day 1 and day 15. Given that social experience is critical for neurobehavioral development in adolescents, we performed the second study using group-housed adolescent and adult rats. In both studies, we observed no age differences in oxycodone self-administration and incubated oxycodone seeking on abstinence day 15. However, on abstinence day 1, we observed decreased oxycodone seeking in adolescents compared with adults. This pattern of data led to elevated incubation slopes in adolescent rats compared with adult rats. Finally, group-housed rats exhibited attenuated oxycodone seeking compared with single-housed rats on abstinence day 15, but not day 1. Taken together, these data suggest that adolescents may be resistant to oxycodone relapse during early abstinence, but this resistance dissipates quickly during the transition between adolescent and young adulthood. In addition, group-housing plays a protective role against incubated oxycodone craving.